The Influence Of Leadership, Motivation And Work Discipline On Employees' Performance At The Regional Government Office Of Bengkulu Province - Deva Ameilia; Sulisti Afriani; Rina Trisna Yanti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
Performance is a benchmark for employees in carrying out tasks that are targeted for completion. Efforts to carry out performance assessments become important by investigate the right performance measurements. To improve the performance, you must pay attention to leadership, motivation and work discipline. The aim of this research is to determine the influence of Leadership, Motivation and Work Discipline on employees’ performance at the Regional Government Office of Bengkulu Province. The type of research is quantitative, the sample in this research is 50 employees at the Regional Government Office of Bengkulu Province. Data collection uses a questionnaire and the analysis methods used are multiple linear regression, determination tests and hypothesis tests. The research results show that the Leadership variable (X1) shows t count 4.164 > t table 1.676 and it is significant 0.000 < 0.05, so the results of the hypothesis Ha is accepted and Ho is rejected, meaning that Leadership (X1) has a positive and significant influence on Performance (Y). The Motivation variable (X2) shows t count 2.975 > t table 1.676 and it is significant 0.005 <0.05, so the results of the hypothesis Ha is accepted and Ho is rejected, meaning that Motivation (X2) has a positive and significant effect on Performance (Y). The Work Discipline variable (X3) shows t count 5.580 > t table 1.676 and is significant 0.000 < 0.05, so the hypothesis results Ha is accepted and Ho is rejected, meaning Work Discipline has a positive and significant influence on Performance (Y). The results of simultaneous hypothesis calculations show that significant value of 0.000 < 0.05, meaning that together X1 (Leadership), X2 (Motivation), X3 (Work Discipline) have a positive and significant influence on Performance (Y).